Equipamento para quartos séniores de residências de serviços acompanhados ou domiciliários : projecto de desenvolvimento com a colaboração da empresa Mundinter S.A. - Moutinho, Andreia Sofia Afonso, 1990- (2016)
The presente study, entitled “Equipamento para quartos séniores de residências de serviços acompanhados ou domiciliários”, consists on a development of a new furniture line for Mundinter SA. This project aims to improve the quality of life of individuals with special needs. This social duty is to integrate, temporarily or permanently, elderly or disabled people, contributing to their balance and well-being. Focused in the social economy (nursing homes, assisted and private residences) and aware the care to be provided to the elderly and dependent it is intended, together with Mundinter S.A., create more versatile and appealing furniture equipment for rooms. The interest in this topic is based on the analysis of the space and equipment functions / purpose, as well as the user’s needs. Through contextualization we try to find solutions allied to the design, though in enormous expansion with society influence, is still unexplored in furniture equipment for elderly or disabled people